Investigation of the vortex dynamics of Fe1.02Se crystals by fundamental and 3rd harmonic ac magnetic susceptibility analysis. (28th January 2015) - Buchkov, K; Polichetti, M; Nenkov, K; Nazarova, E; Mancusi, D; Balchev, N; Kovacheva, D; Zahariev, A; Pace, S
Abstract: The superconducting properties of mm-sized Fe1.02 Se crystals grown by a flux method are investigated. The structural and morphological features are studied by x-ray diffraction (XRD) and by scanning electron microscopy-energy dispersive x-ray spectroscopy SEM-EDX analysis, which identified a co-growth of a dominant superconducting tetragonal phase, with the minority of a non-superconducting hexagonal phase. The ac magnetic response is analyzed using a combined method of the fundamental and the 3rd harmonic ac magnetic susceptibility as a function of the temperature at different ac magnetic field amplitudes and frequencies and with various superimposed dc fields. The variation of the ac magnetic field and frequency in different ranges especially affects the 3rd harmonic components, which are more sensitive to the changes in the flux dynamic regimes. This allows a fine observation of the evolution of the different linear and non-linear processes responsible for the ac magnetic response of the Fe1.02 Se crystals. At low enough ac amplitudes and frequencies, and even in high imposed dc magnetic fields, the Fe1.02 Se crystals show a typical critical state behavior, marking a high stability of the pinning, with very small influence of the vortex dynamical processes. With the change of ac field amplitude and frequency a gradual crossover is observed from the initial stable pinning state through the domination of the intermediate regimes as flux creep and finally to the complete dominance of flux flow. The ac magnetic response is also influenced by geometric edge barrier effects arising from the plate-like geometry of the Fe1.02 Se crystals. The changes of the dominant irreversible (non-linear) mechanism from surface pinning to bulk pinning or to prevailing dynamical regimes is also identified by analyzing the behavior of the 3rd harmonic components.